Efektivitas Krisis Moneter, Nilai Tukar, dan Inflasi terhadap Pertumbuhan Ekonomi di Indonesia - Fitriani, Desita; Setiwati, Ririt Iriani Sri (Jurnal Bisnis Indonesia, 2024)
The purpose of this study was to determine the effectiveness or influence of the monetary crisis,exchange rates and inflation on economic growth in Indonesia. The research method used isqualitative research with library research. Literature study is an analysis that originates from theanalysis of textbooks and previous research. The results of the study show that the monetary, exchangerate, and inflation crises have had a positive effect on economic growth in Indonesia.Keywords: Monetary Crisis; Exchange Rate; Inflation; Economic Growth